The Role of Overconfidence and Risk Perception in Stock Investment Decision-Making among Young Investors - Nico Pracahya; Lucia Rini Sugiarti; Fendy Suhariadi (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The rapid growth of stock market participation among young investors, particularly Generation Z, has intensified concerns regarding the psychological factors underlying investment decision-making. Despite increased access to financial information and digital trading platforms, young investors often exhibit biased judgments and inconsistent decision quality. From a psychological perspective, cognitive biases and subjective risk evaluation play a critical role in shaping behavior under uncertainty. This study aims to examine the role of overconfidence and risk perception in stock investment decision-making among young investors. This research employs a quantitative, explanatory design using survey data collected from 159 Generation Z investors. Data were analyzed using multiple linear regression analysis to assess the effects of overconfidence and risk perception on stock investment decision-making. Overconfidence and risk perception were measured as psychological constructs reflecting cognitive bias and subjective risk appraisal, respectively. The results indicate that overconfidence has a positive and statistically significant effect on stock investment decision-making, suggesting that excessive self-belief increases decisiveness and investment engagement among young investors. Additionally, risk perception significantly influences investment decisions, highlighting the importance of subjective risk evaluation in guiding behavior under uncertainty. The findings confirm that psychological factors jointly shape how young investors interpret information and make financial decisions. From a psychological standpoint, this study contributes to decision-making and cognitive psychology by demonstrating that investment behavior among young adults is driven not only by rational evaluation but also by cognitive bias and perceived risk. The findings imply that psychological interventions such as bias awareness training, self-reflection, and risk appraisal education are essential complements to financial literacy programs.